Analisis Pengaruh Kedalaman Dan Diameter Lubang Bor Terhadap Hasil Peledakan Di Tambang Terbuka - Tesi; Rafiuddin; Syamsuddin (Journal Teknik Dan Teknologi, 2026)
Blasting is an important stage in open-pit mining aimed at breaking rock material to facilitate excavation and loading processes. Fragmentation quality is influenced by blasting design parameters, particularly the depth and diameter of blast holes. This study used drilling geometry data, blasting geometry, explosive consumption, and fragmentation results analyzed using Split Desktop software to determine the effect of variations in blast hole depth and diameter on fragmentation distribution. The results showed that greater blast hole depth produces finer fragmentation due to increased blasting energy. Larger blast hole diameters also increase explosive loading capacity, resulting in more evenly distributed blasting energy. The proper combination of blast hole depth and diameter produces optimal fragmentation in accordance with company operational standards.